Futures past: Economic forecasting in the 20th and 21st century - Ulrich Fritsche; Roman Köster; Laetitia Lenel (Peter Lang, 2020)
Few areas in economics are as controversial as economic forecasting. While the field has sparked great hopes for the prediction of economic trends and events throughout the 20th and 21st centuries, economic forecasts have often proved inaccurate or unreliable, thus provoking severe criticism in times of unpredicted crisis. Despite these failures, economic forecasting has not lost its importance. Futures Past considers the history and present state of economic forecasting, giving a fascinating account of the changing practices involved, their origins, records, and their implications. By bringing together economists, historians, and sociologists, this volume offers fresh perspectives on the place of forecasting in modern industrial societies, thereby making a broader claim for greater interdisciplinary cooperation in the history of economics.
Keywords: 330; History; Research and development management; Economic history; Business studies; general; Public finance and taxation; Development economics and emerging economies; International economics; Industry and industrial studies; Wirtschaftsprognose; Ökonomische Ideengeschichte; Zukunft